Menumbuhkan Minat Baca Anak melalui Penyediaan Pojok Baca dan Metode Reading Aloud di Desa Kutalanggeng Karawang - Rukajat, Ajat (Al-DYAS, 2024)
Reading is one of the types of writing language skills, and the interest and habit of reading among Indonesian society are relatively low. The goal of this Community Service (PkM) is to understand the process, inhibiting factors, driving factors, and teachers' efforts in fostering children's reading interest through the provision of reading corners. The theories underlying this PkM include: non-formal education, the nature of early childhood, reading interest, storytelling methods, storytelling techniques, and storytelling and reading interest. The PkM method used is descriptive method, and the techniques used are observation, documentation study, questionnaire, interview, with a total sampling of 52 children. Based on the PkM findings, it is found that: 1) There is a reading corner and sufficient supporting books, 2) storytelling activities with reading aloud techniques, 3) difficulties in using storytelling methods in the process of fostering reading interest, 4) efforts in fostering children's reading interest carried out by teachers. It can be concluded that within a week, teachers tell stories less than 3 times with a duration of 10-15 minutes. Supporting factors include the availability of storybooks in the reading corner, inhibiting factors include choosing interesting storybooks, and conditioning children during storytelling. Teachers' efforts in fostering children's reading interest are through storytelling with reading aloud techniques and communicating with parents.